2009
DOI: 10.1071/wr08061
|View full text |Cite
|
Sign up to set email alerts
|

Field test of a single-injection gonadotrophin-releasing hormone immunocontraceptive vaccine in female white-tailed deer

Abstract: The development and use of safe, effective and practical wildlife contraceptive agents could reduce reproduction in locally overabundant deer populations in situations where traditional management tools such as regulated hunting cannot be employed. GonaCon Immunocontraceptive Vaccine (the commercial name for a particular gonadotrophin-releasing hormone (GnRH)-based emulsion) was tested in adult female white-tailed deer in a fenced herd near Silver Spring, Maryland, USA. Observations of udder condition were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 42 publications
4
45
1
Order By: Relevance
“…However, in contrast to our measurements, Killian et al [12] showed a weak inverse relationship between contraceptive efficacy of the vaccine and antibody levels: increasing effectiveness with decreasing antibody titers. Their result is difficult to explain biologically in light of our observations and others [24,43] that support a strong positive association between infertility and antibody levels. Their finding may be an artifact of small sample size.…”
Section: Discussioncontrasting
confidence: 65%
“…However, in contrast to our measurements, Killian et al [12] showed a weak inverse relationship between contraceptive efficacy of the vaccine and antibody levels: increasing effectiveness with decreasing antibody titers. Their result is difficult to explain biologically in light of our observations and others [24,43] that support a strong positive association between infertility and antibody levels. Their finding may be an artifact of small sample size.…”
Section: Discussioncontrasting
confidence: 65%
“…For instance, GonaConÔ did not affect bodyweight or blood chemistry of black-tailed prairie dogs (Cynomys ludovicianus) (Yoder and Miller 2011) and blood chemistry in white-tailed deer (Killian et al 2006b). However, other studies in whitetailed deer, cats and elk reported that animals treated with GonaConÔ developed palpable non-painful injection site granulomata or sterile abscesses that did not seem to affect the welfare of the animals (Killian et al 2006b;Curtis et al 2008;Gionfriddo et al 2009;Levy et al 2011). The granuloma at the injection site plays a prime role in the host's defence against the 'chronic infection' represented by a multiyear immunocontraceptive and is considered necessary to the efficacy of the adjuvant .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies suggested that the effectiveness of GonaconÔ, measured as the proportion of individuals rendered infertile, was greater in captivity than in field trials. For instance GonaConÔ caused infertility in 80% (n = 5) of captive white-tailed deer (Odocoileus virginianus) for five years ) but a subsequent study carried out with freeliving animals (Gionfriddo et al 2009) reported infertility in 88% and 47% of the deer (n = 28) during the first and second year after vaccination. Similarly, in captive wild horses GonaConÔ caused infertility in 94%, 60% and 53% of the mares (n = 15) in Year 1, 2 and 3 following vaccination ) but in freeroaming feral horses GonaConÔ caused infertility in 39%, 42% and 31% of the mares (Gray et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the vaccine will work in some species but not as well or at all in others. GonaCon Ò was developed primarily for application to white-tailed deer, 12,[87][88][89][90] but also works in wapiti, 91 swine, 92 and horses. 50 In the case of GonaCon Ò the longer lasting duration of antibodies has been accomplished by the addition of aromatic amino acids to the structure, which enhances immunogenicity but without interfering with binding to pituitary receptors.…”
Section: Duration Of Contraceptive Actionmentioning
confidence: 99%